Edukasi dan Pelatihan Laporan Perpajakan bagi Perusahaan Starup/UMKM di Kelurahan Nogotirto, Gamping, Sleman - Ulfiyatus Sayiah; Nugraeni Nugraeni (Jurnal Kendali Akuntansi, 2023)
The purpose of this non-profit activity is to educate and support micro, small and medium enterprises (MSMEs) by providing an understanding of the basic concepts of SME taxation and the use of applications related to MSME tax obligations. The 1implementation 1of 1charity 1activities 1takes 1place 1in 1several 1stages. 1The 1first 1stage 1is 1the 1design 1stage 1through 1observation 1and 1preliminary 1discussions. 1The 1second 1stage 1is 1the 1implementation 1of 1activities 1in 1the 1form 1of 1technical 1advice 1and 1guidance, 1carried 1out 1through 1presentation 1of 1material 1and 1practice 1of 1calculating 1and 1reporting 1taxes, 1discussions. 1The third stage is monitoring which aims to answer the problems of SMEs in fulfilling their tax obligations independently. An evaluation step follows, the 1purpose 1of 1which 1is 1to 1evaluate 1the 1activities 1implemented. 1The 1positive 1development 1of 1MSME 1development 1is 1not 1in 1line 1with 1the 1level 1of 1government 1tax 1revenue 1in 1this 1sector. 1This 1is 1because 1MSME 1taxpayers 1do 1not 1fulfill 1their 1tax 1obligations. 1April 12022. 1Information 1on 1MSME 1taxes 1and 1fees 1is 1still 1limited. 1Therefore 1it 1is 1necessary 1to 1support 1the 1development 1of 1SMEs 1also 1in 1the 1tax 1sector. 1During 1the 1COVID-19 1pandemic, 1MSME 1mentoring 1courses 1were 1conducted 1virtually. 1This 1training 1aims 1to 1make 1SMEs 1more 1aware 1of 1taxes 1and 1more 1aware 1of 1their 1tax 1rights and obligations. That way, MSME actors will avoid tax sanctions in the future.